Coca: The History and Medical Significance of an Ancient Andean Tradition - Amy Sue Biondich; Jeremy David Joslin (Emergency Medicine International)
Coca leaf products are an integral part of the lives of the Andean peoples from both a cultural and traditional medicine perspective. Coca is also the whole plant from which cocaine is derived. Coca products are thought to be a panacea for health troubles in regions of South America. This review will examine the toxicology of whole coca and will also look at medicinal applications of this plant, past, present, and future.